Penyebaran Penyakit Kuning pada Tanaman Cabai di Kabupaten Tanggamus Dan Lampung Barat - Sudiono, Sudiono (Politeknik Negeri Lampung., 2013)
Yellow disease is one of the important diseases in chili that caused by a virus and is spread by the tobacco whitefly (Bemisia tabaci Genn.). This study aims to determine the spread of yellow diseases caused by gemini virus on chili plant in Tanggamus and West Lampung district. The results showed that the disease caused by a gemini virus has spread of chili plant in Tanggamus district has spread in cropping chili in four Pekon Campang observation that the disease incidence by 83.33%, the population of whitefly infestation of 5.53 larvae/Plant, Margoyoso of 84.11% and 6.61 larvae / plant, Gisting Bawah by 79.61% and 4.63 larvae/Plant, and Gisting Atas by 84.33% and 7,48 larvae/plant. While in West Lampung district has the disease occurrence Cahya Padang village (Kecamatan Balik Bukit) of 89.9% and 15.38 larvae/plant, Seranggas Village (Kecamatan Balik Bukit) of 86.9% and 13.77 larvae/plant, Kecamatan Batu Tulis by 85.4% and 6.75 larvae/plant, and Kecamatan Sekincau by 85.7% and 9.43 larvae/plant. Keywords : Yellow disease, gemini virus, Bemisia tabaci Genn